Windows Phone 8.1 - Posey, Brien (Que, 2014)
"Windows Phone 8.1 is a huge upgrade-more productive, more powerful, more fun! This easy, plain-English video tutorial gets you 100% up to speed with it, so you can make the most of your new Windows smartphone! Brien Posey guides you through everything that makes Windows Phone 8.1 so great, including its amazing Cortana virtual personal assistant. You'll learn the best ways to use Windows Phone hardware, the Start Screen, Live Tiles, and Action Center ... set up Wi-Fi and email ... manage contacts, calendars, and tasks.. play media and take photos ... use OneDrive storage ... download new apps ... make calls and send text messages ... work with Internet Explorer and Office apps ... connect via Facebook, LinkedIn, and Twitter ... even find a lost phone!"--Resource description page.